1980
DOI: 10.1029/gl007i010p00848
|View full text |Cite
|
Sign up to set email alerts
|

Backscatter measurements of 11‐cm equatorial spread‐F irregularities

Abstract: In the equatorial F‐region ionosphere, a turbulent cascade process has been found to exist that extends from irregularity spatial wavelengths longer than tens of kilometers down to wavelengths as short as 36 cm. To investigate the small‐scale regime of wavelengths less than 36 cm, an equatorial radar experiment was conducted using a frequency of 1320 MHz that corresponds to an irregularity wavelength of 11 cm. The first observations of radar backscatter from 11‐cm field‐aligned irregularities (FAI) are describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 21 publications
2
29
0
Order By: Relevance
“… Weber et al [1978] have shown from airglow observations that these structures indeed map along the magnetic field lines. By using the ALTAIR incoherent scatter radar in the N‐S scanning mode, Tsunoda [1980] has studied the N‐S alignment of electron density structures associated with ESF. Using rocket data, Vickrey et al [1984] have studied the mapping efficiency of the spread F structures along the magnetic field line.…”
Section: Introductionmentioning
confidence: 99%
“… Weber et al [1978] have shown from airglow observations that these structures indeed map along the magnetic field lines. By using the ALTAIR incoherent scatter radar in the N‐S scanning mode, Tsunoda [1980] has studied the N‐S alignment of electron density structures associated with ESF. Using rocket data, Vickrey et al [1984] have studied the mapping efficiency of the spread F structures along the magnetic field line.…”
Section: Introductionmentioning
confidence: 99%
“…VHF-, UHF-and L-band radars near the geomagnetic equator have been used for observations of intense coherent echoes caused by Bragg scatter from field-aligned irregularities (FAIs) with a spatial scale-size of one half of the radar wavelength (e.g., Woodman and LaHoz, 1976;Tsunoda, 1980aTsunoda, , 1983. Spatial patterns of backscatter from FAIs are similar to those of equatorial plasma bubbles, and FAIs are collocated with plasma bubbles which are depletions in the equatorial F region plasma (e.g., Tsunoda, 1980b;Tsunoda et al, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…At Jicamarca, Peru, an incoherent scatter radar (ISR) operating at 50 MHz has been widely used to observe ESF irregularities at 3 m scale size [ Farley et al , ; Woodman and La Hoz , ; Fejer et al ., ]. A handful of radars at different longitudes are used to study ESF: the Advanced Research Project Agency Long‐range Tracking and Identification Radar (ALTAIR) (9°N, 167°E; 155.5 MHz and 415 MHz) [ Tsunoda , , ] and the Christmas Island radar (2°N, 202.6°E; 50 MHz) in the Pacific Ocean [ Miller et al ., ], the São Luís radar (2.59°S, 44.21°W; 30 MHz) in Brazil [ Rodrigues et al ., ], and the Equatorial Atmosphere Radar (EAR) (0.2°S, 100.32°E; 47.0 MHz) in Indonesia [ Otsuka et al ., ]. These radars detect irregularities with scale sizes from 0.36 m to 5 m.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of ESF irregularities at submeter scale size are very scarce. Tsunoda [] used the ALTAIR radar operating in the 415 MHz mode, and Target Resolution and Discrimination Experiment (TRADEX) (1320 MHz), concurrently on 17 July 1979. The ALTAIR radar operated in continuous E‐W scans, and when irregularities were detected, the TRADEX radar was turned on.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation